Digital Transformation in Quality Management Systems in Technology Companies, Link Wireless Case - Peña Gómez, Johan Stiven; Asdraldo Vargas, César (Ingeniería Solidaria, 2022)
The following article is the result of a research that describes a model of digital transformation in quality management systems and its applicability in business areas, as is the case of Link Wireless. To verify its applicability, a study was conducted with a qualitative, descriptive and exploratory approach, from which a diagnosis was made where the initial state of the quality management system as established by the ISO 9001: 2015 standard was established. and the technological capacity of the company to design the best strategy that enhances its capabilities to digitize its processes in order to make the most of its software and hardware tools, achieving a model that can ensure the continuity of the operation of the quality management system with the lowest possible cost.